Evaluating Shelley - Clark, Timothy, 1958-; Hogle, Jerrold E. (Edinburgh : Published by Edinburgh University Press for the University of Durham, 1996)
Fourteen scholars discuss the work of Percy Bysshe Shelley from a late twentieth-century perspective. Unlike Shakespeare or Wordsworth, Shelley has never been fully accepted into the established literary canon. Even in his own day his value as a poet and a thinker was hotly debated, leaving a legacy of uncertainty for future generations. Divided into three distinct sections, this book argues that Shelley was both ahead of and in tune with his time and ours. The first section evaluates Shelley within the wider contexts of politics, education, authorship and literary theory; the second through close reading of individual works; while the third addresses editing and editorial practice. Together, these essays expand our knowledge and understanding of this problematic poet and come to a powerful conclusion.
Gives close readings of the key texts including reassessment of a previously undervalued work. Valuable contributions from leading academics such as Marilyn Butler, Stuart Curran and Donald Reiman mix with new ideas from up-and-coming names in the field. Readership: students, academics and researchers in English Literature, the Romantic movement, poetry and 18th-century studies.
'God, and King, and Law': Anarchic Anxiety and Shelley's Canonical Function / Charles J. Rzepka -- Of Education / Stuart Curran -- Shelley and the Question of Joint Authorship / Marilyn Butler -- Shelley and the Conditions of Meaning / Jerrold E. Hogle -- Shelley and the Revolutionary Left / William Keach -- Shelley after Deconstruction: The Poet of Anachronism / Timothy Clark -- 'What's Aught But as 'Tis Valued?': A Reading of The Sensitive-Plant / Michael O'Neill -- 'Lethean Joy': Memory and Recognition in Laon and Cythna / John Donovan -- The Enigma of 'A Vision of the Sea', or 'Who Sees the Waterspouts?' / Nora Crook -- Shelley's Peter Bell the Third: Relationship and the Canon / John Williams -- Keeping Faith with Desire: A Reading of Epipsychidion / Barbara Charlesworth Gelpi -- Shelley, Dante and The Triumph of Life / Ralph Pite -- Close Your Eyes and Think of Shelley: Versioning Mary Shelley's Triumph of Life / Lisa Vargo.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Shelley, Percy Bysshe, -- 1792-1822 -- Criticism and interpretation; Shelley, Percy Bysshe, -- 1792-1822 -- Critique et interprétation.; Shelley, Percy Bysshe, -- 1792-1822; Shelley, P. B., -- 1792-1822.; 18.05 English literature; POETRY -- European -- English, Irish, Scottish, Welsh; Criticism, interpretation, etc